High-dimensional phenotyping reveals novel macrophage-like and hybrid subsets within murine splenic conventional dendritic cells - Chunqing Yang; Qingjie Xue; Yu Feng; Wenjun Ding; Ying Lu; Qinqin Wang (PLoS ONE, 2026)
Conventional dendritic cells (cDCs) are pivotal antigen-presenting cells (APCs) with critical roles in immune regulation, yet their subset classification remains ambiguous due to phenotypic overlap with macrophages and monocytes, particularly in the spleen. This study employed multi-parametric flow cytometry and clodronate liposome (CL) depletion to systematically re-evaluate splenic CD11c high MHCII high cDCs in C57BL/6 mice. We identified three novel subsets: (1) a tissue-resident T-cell zone macrophage (TZM)-like population (F4/80 inter-low CX3CR1 + MERTK + ) constituting 0.59% of cDC2s with >10-fold CL-depletion resistance ( p < 0.0001); (2) a resident F4/80 high APC subset (CCR2 ⁻ Ly6C⁻) accounting for 2.7% of cDC2s with CL-sensitivity; (3) unconventional CD4⁺CD8α⁺ hybrids present in 2.57% of cDC2 and some cDC1s. These findings demonstrate unprecedented cDC plasticity driven by microenvironmental signals, revising conventional classification frameworks and proposing new targets for DC-based immunotherapies in autoimmunity and cancer. Our phenotypic mapping provides a foundational framework for future functional investigations into these novel subsets.